2001
DOI: 10.1021/ef000256q
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Formation of Aromatic Compounds and Solid Deposition during Thermal Degradation of Jet Fuels in the Pyrolytic Regime

Abstract: The formation of pyrolytic solid deposit, or coke, in the fuel line can be detrimental to the operation of high-speed aircraft. Yet, the formation of coke from the fuel has not been well characterized. The present study has investigated the relationship between the formation of aromatic compounds and solid deposition for three candidates for high-thermal-stability jet fuels at 482 °C (900 °F) with stressing periods up to 2 h. The fuels include one coal-derived (JP-8C), one paraffinic petroleum-derived (JP-8P),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 22 publications
2
65
0
Order By: Relevance
“…When the temperature is higher than 550uC, the polymerization of radicals towards coke deposition becomes obvious [6,10]. This process includes the ring formation and propagation.…”
Section: Analysis Of Coke Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the temperature is higher than 550uC, the polymerization of radicals towards coke deposition becomes obvious [6,10]. This process includes the ring formation and propagation.…”
Section: Analysis Of Coke Precursorsmentioning
confidence: 99%
“…Wickham et al studied the formation of filamentous carbons in supercritical cracking of fuels and analyzed the effect of metals [5]. John et al found that the coke deposition is correlated with the aromatic compounds formed during the cracking reaction [6]. Guo et al studied the properties of formed coke [7].…”
Section: Introductionmentioning
confidence: 99%
“…At temperatures above 400 °C, dissolved oxygen has already reacted and the fuel suffers pyrolytic decomposition, exponentially increasing the deposition rates with temperature and linearly with residence time [7]. At those temperatures, hydrocarbon chains undergo cracking into C1-C4 gases and cycloalkanes, eventually leading to aromatic compounds [8]. As the fuel temperature is increased (usually above 450 °C), dissolved oxygen is depleted and the dominant reaction mechanism in the deposit's formation is pyrolysis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work at Penn State has resulted in significant progress in identifying the remaining critical barriers to realization of coal-based fuels [11][12][13][14][15][16][17][18][19][20]. The overall objective of this project is to examine the characteristics and quality of the streams other than the jet fuel, and what effect those materials would have on the other unit operations in the refinery, the quality and value of the other products.…”
Section: Introductionmentioning
confidence: 99%